Capacity Building Kader “Wani Ngandani” dalam Melakukan Sosialisasi Protokol Kesehatan dan Pemantauan Berkelanjutan (Surveillance) di Kampung Tangguh Wani Jogo Suroboyo, Kelurahan Pacarkeling, Kecamatan Tambaksari, Surabaya - Shrimarti Rukmini Devy; Santi Martini; Mochammad Bagus Qomaruddin (Media Gizi Kesmas, 2024)
Background: Surabaya City is one of the cities in East Java Province with a high-risk zone in the spread of Covid-19 cases. One of them is in Tambaksari District, Pacarkeling Village, an area with confirmed cases of Covid-19. It is known that the community in the region has implemented the 5M health protocol, but the discipline for implementing this behavior is still not optimal. Objective: Therefore, the purpose of this study is to improve the knowledge of Capacity Building Cadres through Wani Ngandani socialization activities in Kampung Tangguh Wani Jogo Surabaya, Pacarkeling Village, Tambaksari District, Surabaya. Method: The research method used in this study is quantitative with design action research, namely training activities on knowledge of how to communicate and conduct surveillance on health cadres as problem solving conditions during the Covid-19 pandemic. The location of the activity is in Pacarkeling Village, Tambaksari District, Surabaya. The implementation of offline training by implementing strict 3M health protocols. The data obtained were analyzed descriptively. Results: The results of the study showed that increasing knowledge and skills in communication methods during the socialization of the 5M Health Protocol can increase the knowledge of health protocols for surveillance in 83% of Wani Ngandani cadres. Conclusion: Then it can be concluded that the results of the Wani Ngandani socialization activities in the Wani Jogo Surabaya Resilient Village environment can provide increased knowledge or Capacity Building for Cadres regarding health protocols. Furthermore, continued training is needed to increase the capacity of health cadres and PKK members, so that the knowledge gained is useful for community participation in health programs in the city of Surabaya.